Em busca de estratégias sustentáveis para o controle de larvas de Aedes albopictus (Skuse, 1894): perspectivas tecnológicas e sociais - Silva, Bruna Queiroz da (2012)
Artificial chemical larvicides are a commonly used solution to control larvae of mosquitoes. However, these substances can have health and environmental impacts. We tested the efficacy of two biological methods to control mosquitoes larvae, the copepod (Mesocyclops oggunus) and entomotoxic bacteria Bacillus thuringiensis var, israelensis (Bti). These biological agents were used in isolation and consociated. We also interview endemic control agents that work with Aedes aegpty control in the city of João Pessoa-PB in order to access their perceptions about the uses of biological control against mosquito larvae. We found that the consociation between M. oggunus and Bti is more effective that each method in isolation to control larvae of A. albopictus (a species with similar biology with A. aegpity). Consequently the consociation between copepods and Bti represent a low operational cost and low environmental impact alternative to chemical larvicides in order to control mosquito larvae. Our interviews with endemic control agents involved with Aedes control showed that more efforts are need to inform them about the consequences and precautions associated to the use of chemical larvicides.